Floods and reservoir safety (ICE Publishing, 2015)
"This fourth edition of Floods and reservoir safety provides authoritative guidance on flood protection standards, flood magnitude and freeboard, which is essential for engineers who are responsible for the design and inspection of reservoirs"--Page 4 of cover
First edition published 1978.
Keywords: Reservoirs -- Safety measures -- Standards -- Great Britain.; Reservoirs -- Law and legislation -- Great Britain.; Flood control -- Great Britain.; Flood control -- Law and legislation -- Great Britain.; elektronické knihy; electronic books